Is it possible to differentiate between 2-phenylaminodihydro-1,3-thiazine from 2-phenyliminotetrahydro-1,3-thiazine by spectral methods? New glance to the old problem - Eshimbetov, Alisher; Adizov, Shahobiddin; Kaur, Inderpreet; Reymov, Akhmed (European Journal of Chemistry, 2021)
Several studies have reported the presence of amine and imine tautomeric forms for hydrogenated 1,3-thiazine derivatives. However, identification of their tautomeric forms by UV, FTIR and mass-spectral methods does not yield expected results. Here, we report the synthesis of 2-phenylaminodihydro-1,3-thiazine and 2-phenyliminotetrahydro-1,3-thiazine and the analysis of their UV, FTIR and NMR (1H and 13C) spectral data. An identical picture of UV spectra was recorded for both compounds. However, distinctive characteristics were found in the FTIR, 1H and 13C NMR spectra. The C=N band of amine form was observed in higher frequency region relative to imine form. The signal of C2 carbon of amine form in 13C NMR spectrum was occurred in more downfield (δ 165.3 ppm) relative to C2 signal of imine form (δ 152.1 ppm). In addition, the difference between C2 and C8 carbon signals of amine form was very high (Δδ = 30.6 ppm) relative to imine form (δ 5.4 ppm). The position of C2 and C8 signals and the difference between them in 13C NMR spectrum was found to be more promising in identification of tautomeric forms in case of hydrogenated 1,3-thiazine derivatives.